2020
DOI: 10.3390/genes11010112
|View full text |Cite
|
Sign up to set email alerts
|

SNP Diversity in CD14 Gene Promoter Suggests Adaptation Footprints in Trypanosome Tolerant N’Dama (Bos taurus) but not in Susceptible White Fulani (Bos indicus) Cattle

Abstract: Immune response to infections has been shown to be mediated by genetic diversity in pattern recognition receptors, leading to disease tolerance or susceptibility. We elucidated naturally occurring variations within the bovine CD14 gene promoter in trypanosome-tolerant (N’Dama) and susceptible (White Fulani) cattle, with genomic and computational approaches. Blood samples were collected from White Fulani and N’Dama cattle, genomic DNA extracted and the entire promoter region of the CD14 gene amplified by PCR. W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 60 publications
0
4
0
Order By: Relevance
“…The GERP scores were negative, indicating that substitutions occur at a rate that is greater than neutral, suggesting that substitutions are tolerated in these locations, and it is likely that they are not detrimental. The variants may even be beneficial, as previously described in which similar variation in mature miRNAs targeted CD14 gene, thus regulating its expression during bovine trypanosomosis (Morenikeji et al, 2020). Further work is needed to validate these predictions with in vitro analyses examining miRNA expression, binding, and their effect on the host immune response to bovine coronaviruses.…”
Section: Discussionmentioning
confidence: 81%
“…The GERP scores were negative, indicating that substitutions occur at a rate that is greater than neutral, suggesting that substitutions are tolerated in these locations, and it is likely that they are not detrimental. The variants may even be beneficial, as previously described in which similar variation in mature miRNAs targeted CD14 gene, thus regulating its expression during bovine trypanosomosis (Morenikeji et al, 2020). Further work is needed to validate these predictions with in vitro analyses examining miRNA expression, binding, and their effect on the host immune response to bovine coronaviruses.…”
Section: Discussionmentioning
confidence: 81%
“…Probably this phenomena of higher transversions is NR 6-1 specific, which has led to more number of amino acid changes, though they were tolerated in the functional domains of the enzyme and functionality was retained. However, such a higher rate of transversion in the gene does exist, e.g, CD14 gene in Bos taurus and Bos indicus (Morenikeji et al 2020); MYB gene in chickpea (Roorkiwal et al 2014) etc.…”
Section: Discussionmentioning
confidence: 99%
“…[3]. The previous studies [4][5][6][7] have shown that certain cattle breeds, such as N'Dama are trypanotolerant with the ability to control parasitemia and anemia, thus harboring the parasite and serving as reservoir hosts. This is thought to be an evolutionary adaptation that the N'Dama breed acquired, upon exposure to trypanosomiasis after being introduced to sub-Saharan Africa.…”
Section: Introductionmentioning
confidence: 99%